2003
DOI: 10.1097/00000658-200303000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These results show that there are no differences between the two types of treatment with respect to preventing BE from progressing to dysplasia and adenocarcinoma. However, successful antireflux surgery proved to be more efficient than medical treatment in this sense, perhaps because it completely controls acid and biliopancreatic reflux to the esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The results of one trial indicated that successful surgical treatment was better than medical treatment in preventing BE from progressing to dysplasia and adenocarcinoma [17]. However, it may not be appropriate to compare the results of the subgroup of patients who underwent successful surgery with those of the entire medical group because this would introduce bias, since a substantial proportion of patients under medical therapy continued to have pathological levels of acid and biliary reflux [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of one trial indicated that successful surgical treatment was better than medical treatment in preventing BE from progressing to dysplasia and adenocarcinoma [17]. However, it may not be appropriate to compare the results of the subgroup of patients who underwent successful surgery with those of the entire medical group because this would introduce bias, since a substantial proportion of patients under medical therapy continued to have pathological levels of acid and biliary reflux [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is as yet no definitive endpoints for the treatment of BE in the current literature. Only two randomized controlled trials evaluated the risk of progression to cancer, and these concluded that successful surgery and PDT may be effective treatments for reducing the onset of cancer [17,21]. In future studies, the endpoints for treatment modality should be standardized, and a long period of follow-up is needed to determine whether medical treatment, antireflux surgery, and ablative therapy have an impact upon the malignant progression of BE to adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further adenocarcinomas in Barrett's esophagus under medication with proton pump inhibitors have been reported. The prospective randomized trial of Parrilla comparing medication and fundoplication in the prevention of neoplasia or adenocarcinoma resulted in equal numbers of adenocarcinomas in both groups [32]. The interpretation without the intention to treat principle …”
Section: Prevention By Antireflux Surgery or Medicationmentioning
confidence: 99%